Unhealthy snack intake modifies the association between screen-based sedentary time and metabolic syndrome in Brazilian adolescents - Camila Wohlgemuth Schaan; Felipe Vogt Cureau; Deborah Salvo; Harold W. Kohl; Beatriz D. Schaan (BMC, 2019)
Abstract Background Excessive screen time has been associated with metabolic syndrome (MetS) among adolescents; however, snack intake in front of screens may play a role in this association. Therefore, our objective was to investigate the association between screen-based sedentary time with MetS and whether this association is modified by unhealthy snack intake in front of screens. Methods This study was a nationwide, cross-sectional, school-based survey in Brazil including adolescents aged 12 to 17 years. The frequency of snack consumption in front of screen and screen-based sedentary time (TV view, computers and videogames use) were self-reported. Thereafter, screen time was categorized (≤2, 3-5 and ≥ 6 h/day); snack consumption in front of screens was dichotomized. Metabolic syndrome diagnosis was defined based on the International Diabetes Federation criteria. Associations between screen time and MetS were investigated using logistic regression in overall sample and after stratification by snack intake in front of screens. Results A total of 33,900 adolescents were included in the analysis. The final adjusted model, which included sociodemographic data, physical activity, and energy intake, showed that adolescents who spent ≥6 h/day in front of screens had an increased odds ratio for MetS (OR = 1.68, 95%CI: 1.03-2.74). However, after stratifying the sample according to reported snack intake, the association between higher screen-based sedentary time and MetS remained significant only for adolescents who reported consumption of snacks in front of screens. Conclusion Longer screen-based sedentary times were directly associated with MetS. However, this association seems to be modified by reported snack intake in front of screens.